I-gel™ Versus LMA-Fastrach™ Supraglottic Airway for Flexible Bronchoscope-Guided Tracheal Intubation Using a Parker (GlideRite™) Endotracheal Tube. (August 2015) - Moore, Alex; Gregoire-Bertrand, Felix; Massicotte, Nathalie; Gauthier, Alain; Lallo, Alexandre; Ruel, Monique; Todorov, Alexandre; Girard, Francois
<x xml:space="preserve">Abstract</x> BACKGROUND: The I-gel™ (IG) supraglottic airway device is a reliable way to establish an airway. Its large ventilation lumen allows for easy passage of an endotracheal tube. With the use of a flexible bronchoscope, the IG offers a good visualization of the laryngeal inlet. This prospective randomized study aims to compare the success rate of flexible bronchoscope-guided tracheal intubation using either the IG or the LMA-Fastrach™ (FT) laryngeal masks. METHODS: One hundred twenty patients requiring general anesthesia were randomized to 1 of the 2 study groups: IG or FT. After anesthesia induction, the assigned laryngeal mask was inserted to obtain adequate ventilation. We then proceeded to a flexible bronchoscope-guided intubation through the supraglottic device. Tracheal intubation and laryngeal mask insertion success rates were noted, as well as the time required for these manipulations. The view of the laryngeal inlet was graded for each intubation attempt. RESULTS: Sixty patients were assigned to each study group. The intubation success rates were similar between the IG and the FT groups (100 % vs 95.0 % at first attempt; P = 0.12). The times required for tracheal intubation were significantly lower in the IG group (30 ± 11 seconds vs 50 ± 21 seconds; P < 0.0001). Glottic visualization was better in the IG group, with a significantly higher percentage of grade 1 visualization (63.3% vs 3.3%; P < 0.0001) and a lower percentage of grade 3 visualization (1.7% vs 60.0%; P < 0.0001), than that in the FT group. CONCLUSIONS: The use of the IG supraglottic airway device as a conduit for flexible bronchoscope-guided tracheal intubation results in a success rate equivalent to the use of the LMA-FT™. However, the IG allows for shorter intubation times and a better visualization of the glottic opening compared with the LMA-FT™.